(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article talks about the development of the cotton industry in Karakalpakstan in the years after the Second World War. The effect of the policy carried out in the agrarian sector on the development of the society is considered. It is said that 1263 units of new aggregates and mechanisms will be installed as a result of the construction of cotton ginning factories and the increase in the volume of work in them, as well as the intensification of products in the factories, and the volume will increase every year.